Mobile crowdSensing privacy - Guarda, Teresa (2019)
Information and communication technologies have been evolving rapidly, providing more and more alternative ways of accessing information, accessible through multiple paths and devices, transforming IoT into a giant digital system. This heterogeneous diversity ecosystem allows travel to the CrowdSensing era. Information in its role of reducing uncertainty is responsible for finding ways and shortcuts that increase efficiency and reduce the waste of time in the decision-making process. The massive spread of IoT devices has led to CrowdSensing, a sensor-based ecosystem of many different formats and technologies, in which information created by sensors is essential for decisionmaking processes and for improving business process efficiency. Service providers are beginning to design new business models that consider the smart things scenario, providing sensing as a service (SaaS). This article aims to provide insight into the Mobile CrowdSensing application environment by focusing on issues related to privacy of participant.